2016
DOI: 10.3402/qhw.v11.30534
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lifestyle habits on quality of life in patients with established rheumatoid arthritis—A constant balancing between ideality and reality

Abstract: IntroductionRheumatoid arthritis (RA) is a chronic, inflammatory, and systemic disease with symptoms that limit activities and affect quality of life. RA is associated with an increased risk of developing comorbidities, some of which are also known to be associated with lifestyle habits such as physical activity, diet, smoking, and alcohol. There has been an augmented focus on the implementation and maintenance of healthy lifestyle habits even for patients with RA in the past decade, but little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 43 publications
(51 reference statements)
2
48
0
5
Order By: Relevance
“…Specifically, they could help patients to consider what types of signs to look for, explore with patients the right amount of body listening to do to improve or manage their health without it becoming an onerous task, and counsel them to reduce experiences of information overload and powerlessness. This aligns with a study of rheumatoid arthritis patients, which reported that patients struggled to balance their ideals with reality, and suggested that providers work with patients to develop the right balance of lifestyle habits (Malm et al, 2016). …”
Section: Discussionsupporting
confidence: 83%
“…Specifically, they could help patients to consider what types of signs to look for, explore with patients the right amount of body listening to do to improve or manage their health without it becoming an onerous task, and counsel them to reduce experiences of information overload and powerlessness. This aligns with a study of rheumatoid arthritis patients, which reported that patients struggled to balance their ideals with reality, and suggested that providers work with patients to develop the right balance of lifestyle habits (Malm et al, 2016). …”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, because smoking has also been associated with increased disease activity, its actions may be beyond initiation of RA (63). Thus, a major unanswered question regarding the role of smoking in RA is where it acts in the natural history of RA.…”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…Furthermore, because smoking has also been associated with increased disease activity, its actions may go beyond the initiation of RA [27]. Thus, a major unanswered question regarding the role of smoking in RA is where it acts in the natural history of RA.…”
Section: Smoking As a Risk Factor For Rheumatoid Arthritismentioning
confidence: 99%